Sosialisasi Nilai-Nilai Bela Negara Di Yayasan Al Kamilah - Asep Kamaluddin Nashir; Rizky Hikmawan; Sekarwati (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Parents are parties who cannot be excluded in education. They are the first school for children. For this reason, it is the responsibility of parents to be able to educate their children so that they grow into successful people in the future. One form of children's success is when they are able to become strong individuals who can play a positive role in the development of the nation and state. For this reason, parents also need to instill the values of patriotism in their children from a young age. However, many parents have limitations in understanding the values of patriotism. Therefore, it is necessary to disseminate the values of patriotism to parents to make it easier for them to implement them with their children in their daily lives. In this Community Service, the values of patriotism will be socialized to the parents of students at the Al Kamilah Foundation.